New legal minimum ages for final felling : consequences and forest owner attitudes in the county of Västerbotten - Lindskog, Martin (SLU/Dept. of Forest Resource Management, 1998)
The Forestry Act was altered in Sweden the 1st of January 1994, replacing the 1980 forest legislation. Several deregulations were made and one of them was the lowering of the legal minimum age (LMA) for final felling. The authorities naturally show interest in the effects of the new legislation, and the present thesis is a contribution in this respect. The work was initiated and commissioned by the County Forestry Board of Vasterbotten in November 1996. The main purpose was to study the behaviour of forest owners with respect to the new LMA, but a more general attitude research about the LMA was included as well. The issues were studied for eight (of sixteen) County Ranger Districts in the county of Vasterbotten. Forest owners were classified as private or companies and as inland or coastal. The results are based on a sample of about 40 final fellings from each of the two owner categories and each district. In a subset, the forests cut were aged between the old and the new LMA, and the correspondning set of forest owners constitutes the sample for the the attitude research. The estimated percentage in area of the final fellings that falls between the present and the former LMA is marked but varies considerably between owner categories and especially between districts within category. The estimated percentage varies between 0 % and 60 % over all districts and owner categories. Averaged over districts the percentage varies between 17 % and 25 % for the four categories. The highest figure was obtained for coastal private forest owners, while the other three categories showed similar values. Noteworthy is the large and significant differences between the districts, for each of the four categories. The results of the attitude research indicates that roughly 50 % of the respondents were not aware of the lowering of theLMA and 75 % of the respondents were not aware of that the stand they cut were below the old LMA. Seemingly, inland private owners are more aware of the changes in the law. It appears that they act more like the legislator intended. An explanation to this could be a good communication with the County Ranger Districts. In general terms a better communication between forest owners and the authorities would improve the implementation of the forestry legislation.